Subsistence via Jala-Samadhi (Sacred Suicide): An Enigmatic Activism of Yogmaya - Shrestha, Tara Lal (Tribhuvan University Journal, 2023)
Collective jal-samadhi (killing oneself by plunging in the river) is one of the rare evidences in the resistance history that Yogmaya led from the Eastern part of Nepal at the verge of Rana regime. This paper examines her three different aspects - her life story, her Sarwartha Yogbani, and her collective jala-samadhi - to argue Yogmaya as an enigmatic social activist. The main purpose is to foreground her life struggle with reference to her Sarwartha Yogbani from the perspective of subaltern studies. The notions of ‘hegemony’ and ‘subaltern’ as Antonio Gramsci and Gayatri Chakravorty Spivak point out when ‘agency’ of the oppressed is concerned have been applied as theoretical parameters to foreground her story. The finding of the study shows subsistence of her resistance via jal-samadhi that helps engage intellectuals in academic activism and critical discourse in the history form below perspective.